Dual functional hetero-anthracene based single component organic ionic conductors as redox mediator cum light harvester for solid state photoelectrochemical cells. Issue 11 (1st March 2018) - Vaghasiya, Jayraj V.; Sonigara, Keval K.; Soni, Saurabh S.; Tan, Swee Ching
Abstract : We have synthesized a novel solid organic ionic conductor (SOIC) that acts as a redox mediator and a light absorbing material at the same time. Abstract : We have synthesized a novel solid organic ionic conductor (SOIC) that acts as a redox mediator and a light absorbing material at the same time. Such dual function of SOICs has not been reported before. It was achieved by substituting N, N ′-dimethyl benzimidazolium iodide (BIMI) with hetero-anthracene (phenoxazine (POZ)/phenothiazine (PTZ)) which are labeled as SOIC-1 and SOIC-2, respectively. These substitutions caused the absorption spectrum of BIMI to be extended over 100 nm into the red spectrum and at the same time exhibit excellent redox capability and ionic conductivity. In addition, these synthesized SOICs also enhance the total electron injection into the TiO2 matrix with the metal-free SK3 dye sensitizer. Density functional theory (DFT) was used to optimize the structure and geometrical arrangement of the SOICs. To evaluate the role of PTZ/POZ substitution on BIMI and how pore filling can affect the device performance, solid-state DSSC (ss-DSSC) devices were prepared with two different thickness of TiO2 (8 μm and 12 μm) photoanode. The 8 μm thick TiO2 photoanode with SOIC-1 has an overall PCE of 7.9% which is about 72% higher than the unmodified BIMI (PCE of 4.4%) under AM1.5 illumination. Last but not least, the synthesized SOICs have high thermal stability up to 120 °C which is way beyond the operating temperatures of solar cells which make them ideal for real-world applications.